Educational action on breastfeeding in the PROAME group in a Basic Health Unit (Research, Society and Development, 2022)
Exclusive breastfeeding is when the baby's diet is restricted to the consumption of breast milk, from birth to six months of life, it is the necessary nutrition for the child, with no need to add other foods and liquids. Adequate guidance for pregnant and lactating women regarding breastfeeding in the context of primary care has strong positive influences on the breastfeeding process, adherence and continuity. This study seeks to report the experience of nursing students, from the Paraense Academic League of Nursing in Women's Health and Obstetrics, based on an educational health activity with lactating mothers from the Exclusive Breastfeeding Program group of a Municipal Health Unit. The present study is a descriptive research, of a qualitative nature, of the experience report type, developed by undergraduate Nursing students. The actions developed aimed at transmitting to pregnant women information related to breastfeeding, importance, advantages, as well as support and guidance on expressing and the correct storage of breast milk. When analyzing the report, it was observed that the topics addressed in the group are of paramount importance, as it generated doubts and interest on the part of the mothers present, even among those who already had certain knowledge on the subject. Furthermore, it is worth mentioning that the lecture and the conversation circle allowed the participation of these women in the dynamics, as well as the questions directed to this audience about difficulties in breastfeeding, which allowed the doubts that still existed on this topic to be clarified and resolved.